Coherence and Cohesion in Narrative Text Written by EFL Students - Ni Luh Wiji Adnyani Putri; Dewa Putu Ramendra; Putu Adi Krisna Juniarta (Journal of Educational Study, 2025)
This study aims to provide analysis and presentation related to coherence and types of cohesion in narrative texts of grade eleven at SMA Negeri 1 Seririt in the 2024/2025 academic year. This study employs a mixed-method design, specifically an explanatory sequential mixed-method design, which integrates quantitative and qualitative descriptive methods. The findings of the analysis indicate that students have good abilities in building coherence in their writing, with details of 53% of students having very good abilities, and 47% of students having good abilities. students also frequently use employ various type of cohesion, such as references, Conjunction, substitutions, and lexical cohesion. This is indicated by the number of students who use the words she, he, they, and, since, but, day and others, all of these words are forms of cohesion. Furthermore, the type of cohesion most widely used by students is references, which reaches 50.3%. conjunctions were found as much as 28.2%, substitution as much as 0.18% and lexical cohesion as much as 21.2%. From the overall analysis it was concluded that the coherence in the texts can be influenced by the generic structure of the texts, the relationship between paragraphs, and the appropriateness and consistency of the topic of each paragraph. The cohesion observed in students' writing also demonstrated their existing comprehension of the development of relationships between words, phrases and sentences.